Conceptual thermal constraints on the growth of the first tree on a terraformed Mars - Agnieszka Wendland; Piotr Pałka; Robert Olszewski; Alison F.C. Bridger; Melinda A. Kahre; Christian Körner; Christopher P. McKay (PLoS ONE, 2026)
The environmental conditions on present‑day Mars are far outside the range tolerated by known complex terrestrial life. Conceptual climate studies have suggested that, in hypothetical terraforming scenarios, artificially enhancing the greenhouse effect could restore Mars to more habitable surface conditions. Early colonizing terrestrial life on a warming Mars would plausibly consist of lichens and high‑alpine or high‑arctic plants. Here, we consider a later, more demanding step and investigate the thermal conditions under which the first tree could, in principle, grow on the Martian surface. Based on empirical treeline studies, we adopt thermal thresholds for a representative high‑elevation conifer: a growing season of at least 110 sols during which daily minimum temperatures exceed −6 °C, daily means exceed 6 °C, and daily maxima remain below 40 °C. In addition to liquid water and suitable substrates, O₂ at ~1 hPa and non‑toxic CO₂ levels are likely required; however, these non‑thermal constraints are not explicitly modelled and make the temperature thresholds necessary but not sufficient for tree viability. We use a high‑resolution surface energy balance model of Mars, assuming a pure CO₂ atmosphere with prescribed grey infrared opacity and neglecting the coupled water cycle, full atmospheric dynamics, photochemistry, and surface radiation, to estimate spatio‑temporal thermal windows for potential tree growth as a function of CO₂ surface pressure and additional greenhouse forcing. For a 100 hPa CO₂ atmosphere, near‑surface temperatures satisfying the treeline thresholds first appear when the added grey infrared opacity is ~ 0.39 optical depths. In our simulations, these thermal criteria are initially met not in the tropics (±25°), but in the low‑lying Hellas Basin. As either the CO₂ surface pressure or the imposed grey opacity is increased beyond the values required to open the thermal window, large regions of the southern hemisphere subsequently become thermally overheated and thus unsuitable for tree growth. In this sense, the thermal windows identified in our simulations mark conditions under which temperature would no longer be the primary limiting factor for tree growth, assuming that other essential environmental constraints (such as water availability, radiation environment, substrate properties, and atmospheric composition) are satisfied. We emphasize that this study deals with temperature only, which is an important factor in tree growth on Mars. Other factors that affect tree growth, including water, CO₂ limits, O 2 limit, UV and ionizing radiation, and soil nutrients and microbial population, are not considered explicitly here.